Kebutuhan Tenaga Kerja Bagian Filing Berdasarkan Metode ABK Kes di RSUD dr. Moewardi - Nopita Cahyaningrum; Yeni Tri Utami; Eni Nur Rahmawati; Bayu Suryo Nagoro (Jurnal Infokes, 2021)
Healthcare Workload Analysis is a method of calculating human resource needs based on the workload carried out by each type of healthcare workers according to their main duties and functions. Dr. Moewardi Hospital is a type A hospital that has 7 medical record employees in the filing department and has an increasing trend of patient visits every year. As a result, the workload of employees has increased. This study aims to determine the need for workers in the filing section based on the Healthcare Workload Analysis method. This is descriptive research. Data collection methods employed in this study are observation and interview. The population of this study is all workers in the filing section. Total sampling technique is used to take the samples. The result of this study shows that the public hospital as a healthcare facility with medical record employees in the filing department has available working time is 75,240 minutes/year, standard workload is 2,128,256, FTP value is 1.04% and STP value is 1.01 and workers needed in the filing department in 2020, calculated using the Healthcare Workload Analysis, is 9 workers. The conclusion of this study is that the need for workers in the filing section is 9 workers, while now there are 7 workers there. So that it requires additional workers. The author suggests that it is necessary to hire 2 more workers in the filing section so that the employees’ workload is not excessive and all jobs in this section can be done properly.